Determination of MoCA Cutoff Score in Patients with Alcohol Use Disorders. (19th December 2017) - Ewert, Valérie; Pelletier, Stéphanie; Alarcon, Régis; Nalpas, Bertrand; Donnadieu‐Rigole, Hélène; Trouillet, Raphaël; Perney, Pascal
Abstract : Background: The Montreal Cognitive Assessment (MoCA) score is a convenient and promising tool for estimating alcoholic patients' global cognitive functioning, a major challenge for all specialized alcohol treatment centers. However, whether or not the score should be corrected for education level and whether the proposed cutoff is relevant in patients with alcohol use disorders (AUD) should be determined. Methods: We compared the MoCA scores in patients hospitalized for AUD with and without cognitive impairment assessed by a battery of neuropsychological (NP) tests. Sensitivity, specificity, and cutoff of the MoCA score were analyzed using receiver operating characteristic curve analysis. Results: Thirty‐one patients with and 25 without cognitive impairment were included in the study. There were 40 men and 16 women, with a mean age of 49.5 years. The mean uncorrected MoCA score was 23.1 ± 3.3 in those with and 27.0 ± 1.9 in those without cognitive impairment. NP tests were significantly correlated with the MoCA score. Uncorrected MoCA scores identified more than 80% of the patients with a cutoff score equal to 26, to obtain similar accuracy with the corrected score required using a cutoff score equal to 27. Conclusions: Our results confirm that the MoCA test is a convenient and reliable screening tool to measure cognition defects in alcoholic patients. As using the 1‐point education adjustment increases the cutoff score by 1 point, it is suggested to use the noncorrected score and the usual cutoff, that is, 26. Being easy to administer and only moderately time‐consuming, the MoCA score should be used extensively in addiction treatment centers. Abstract : We determined the best cutoff of the MoCA screening tool of cognition defects in alcoholics. It can be used with or without correction for education level. However, as using the correction increases the cutoff score by one point, it is suggested that the uncorrected score be used with the usual cutoff, i.e. 26. [ROC analysis for the corrected (empirical and smoothed = black and gray dotted lines) (AUC = 0.84; p  < 0.001) and the uncorrected MoCA scores (black and gray full lines) (AUC = 0.87; p  < 0.001)].